1917 N.H. Laws 727-28 - (:unkn) unknown (My University, 1917)
An Act for the Regulation of the Sale and Use of Explosives and Firearms, ch. 185, § 1: No person shall manufacture, sell, or deal in firearms or in gunpowder, dynamite, nitro-glycerine, or other form of high explosive, unless he shall first obtain, from the selectmen of the town or the chief of police of the city where such business is to be conducted, a written license therefor
Keywords: TRANSFER, MANUFACTURE & POSSESSION